2011
DOI: 10.1021/ma202055a
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and Host–Guest Interactions in Dansyl-Substituted Poly(acrylate)s in the Presence of β-Cyclodextrin and a β-Cyclodextrin Dimer in Aqueous Solution: A UV–Vis, Fluorescence, 1H NMR, and Rheological Study

Abstract: The use of fluorescent polymers has been reported in studies of scintillators, 1 luminescent solar concentrators, 2 laser-resistant materials, 3 fiber-optic sensors, 4 and laser dyes. 5 Such polymers usually consist of a backbone substituted with fluorophores such as the naphthyl, 6À9 pyrenyl, 7,10À14 and dansyl 8,15À19 entities. The fluorescence intensities and lifetimes of such fluorophores are sensitive to local environment such that steady-state and time-dependent fluorescence studies have provided conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In NOESY measurements, protons that are in close proximity to each other give rise to correlation peaks. , According to Figure (i), there are correlations between 1 H derived from the dpa–azobenzene unit and H3 derived from the inside cavity of CyD in the presence of 1 equiv of ATP (enclosed in blue circles). The results suggested that conformations including and excluding the CyD-dpa-azobenzene unit exist in equilibrium in solution .…”
Section: Resultsmentioning
confidence: 99%
“…In NOESY measurements, protons that are in close proximity to each other give rise to correlation peaks. , According to Figure (i), there are correlations between 1 H derived from the dpa–azobenzene unit and H3 derived from the inside cavity of CyD in the presence of 1 equiv of ATP (enclosed in blue circles). The results suggested that conformations including and excluding the CyD-dpa-azobenzene unit exist in equilibrium in solution .…”
Section: Resultsmentioning
confidence: 99%
“…We also analyzed the supramolecular conformation of the ATP/ Cu·1 β complex by conducting nuclear Overhauser effect spectroscopy (NOESY) measurements of complex Cu·1 β. In the NOESY measurements, protons in close proximity to each other give rise to correlation peaks [ 43 , 44 ]. Correlations between the protons derived from the adenine moiety of ATP (α and β) and the protons derived from the inside cavity of CyD (H3 and H5) were observed ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…The model used to determine the apparent complexation constant assumed that an equilibrium exists between a-CD, trans Azo-Cl and their complex formed as a host-guest 1 : 1 complex. 44 Therefore, a-CD complexed trans Azo-Cl according to eqn (4). The apparent complexation constant, K, at equilibrium was given by…”
Section: Resultsmentioning
confidence: 99%